2010
DOI: 10.1134/s1070428010060151
|View full text |Cite
|
Sign up to set email alerts
|

Conformational analysis of 5-substituted 1,3-dioxanes

Abstract: Quantum-chemical study on the potential energy surface of 5-alkyl-and 5-phenyl-1,3-dioxanes at the RHF/6-31G(d) level of theory revealed two pathways for conformational isomerizations of the equatorial and axial chair conformers. Potential barriers to this process were estimated. The Gibbs conformational energies ∆G° of substituents at C 5 in the 1,3-dioxane ring were determined on the basis of experimental ( 1 H NMR) and theoretical vicinal coupling constants, which turned out to be consistent with published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…According to the MP2/6-31G(d)//HF/6-31G(d) calculations, the C eq and C ax conformers of III are degenerate in energy. The transition states correspond to half-chair and symmetrical and unsymmetrical boat conformers [20,22]. The obtained data indicated that the concentration of flexible conformers is quite small, and the conformational behavior of dioxanes III-VII may be represented fairly accurately as the binary equilibrium between C eq and C ax .…”
Section: Methodsmentioning
confidence: 90%
See 3 more Smart Citations
“…According to the MP2/6-31G(d)//HF/6-31G(d) calculations, the C eq and C ax conformers of III are degenerate in energy. The transition states correspond to half-chair and symmetrical and unsymmetrical boat conformers [20,22]. The obtained data indicated that the concentration of flexible conformers is quite small, and the conformational behavior of dioxanes III-VII may be represented fairly accurately as the binary equilibrium between C eq and C ax .…”
Section: Methodsmentioning
confidence: 90%
“…Conformational inversion of 5-substituted 1,3-dioxanes III-VII also involves equilibrium between two non-degenerate chair conformers through intermediate minima 2,5-T and 1,4-T (not including enantiomeric structures) [20][21][22] (Scheme 5). In all cases, the global minimum is occupied by C eq , and conformer 1,4-T has the highest energy.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…With the help of non-empiric quantum-chemical approximations the evaluation of stereoelectronic interactions was obtained and the presence of homoanomeric effects in the 1,3-oxathiane ring was established [20,21]. But unlike cyclohexane [22], 1,3-dioxanes [22][23][24][25][26][27][28][29][30][31][32], and 1,3-dithiane [33, 34], pathways of conformational isomerization of 1,3-oxathiane molecules were not considered. In the majority of cases "chair-chair" inversion was postulated [6,[9][10][11][12][13], and in some cases the participation of flexible forms was suggested [14][15][16]18].…”
mentioning
confidence: 99%